Investigating the EKC hypothesis with nanotechnology, renewable energy consumption, economic growth and ecological footprint in G7 countries: panel data analyses with structural breaks. Issue 1 (31st December 2023) - Aydin, Mucahit; Koc, Pınar; Sahpaz, Kadriye Izgi
ABSTRACT: This study investigates the relationship between nanotechnological innovations, renewable energy consumption, economic growth, and ecological footprint for G7 countries within the framework of the Environmental Kuznets Curve (EKC) hypothesis. The study employs panel cointegration tests with structural breaks from 1990–2018. Nanotechnology is expected to reduce environmental degradation by increasing renewable energy consumption and energy saving. In this context, nanotechnological innovations are an essential tool for sustainable development. However, the literature also emphasizes that nanoparticle emissions from nanotechnology can negatively impact human and environmental health in the long term, and these need to be analyzed. In this context, this study is the first to empirically examine the relationship between nanotechnological innovations, renewable energy consumption, economic growth, and ecological footprint within the framework of the EKC hypothesis. The outcomes affirm that all variables are integrated with the long term. The results show that the EKC hypothesis is valid only in the USA. Nanotechnological innovations have a reducing effect on environmental degradation in the USA, whereas; they have an increasing impact on environmental degradation in Italy and the United Kingdom. Renewable energy consumption enhances environmental quality in Italy, Japan, the United Kingdom, and the USA. Based on these empirical findings, the government should pioneer to development of new the lowest nanoparticle-emitting nanotechnologies. And that way, it will be possible to encourage energy savings and renewable energy consumption more safely, and the effectiveness of sustainable development policies will increase.